Unconventional Take-off and Landing Methods - Kong, Wenli; Firat, Mehmet Deniz; Behler, Till (TMAL02 Expert Conference, 2020)
The take-off and landing process is the challenge for an aircraft to start and end the actual flight successfully. It has always been invested a lot of research to make optimization for more comfort, safety, etc. Next to the conventional take-off and landing methods where the aircraft is started and landed at a long runaway by the execution of the pilot, there are – also because of the variety of applications of modern aircraft - a lot of other take-off and landing methods that are required due to the circumstances or even because of better appropriateness or given technology and design. This paper gives a short overview of a few unconventional and modern take-off and landing techniques and presents them regarding application fields, potential and challenges and also focuses on future relevant aspects.